2013
DOI: 10.1063/1.4807054
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic picture of surface charge trapping in semiconductor nanocrystals

Abstract: The current model for understanding trapping of charge carriers to the surface of semiconductor nanocrystals is inconsistent with experimental evidence indicating that carriers can thermally de-trap from surface sites. A proper understanding of the microscopic details of charge trapping would guide chemical design of the nanocrystal surface for applications such as charge transport, sensing, or photochemistry. This thesis presents a model of surface charge trapping in which transitions to surface state are gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 66 publications
(5 reference statements)
7
114
2
Order By: Relevance
“…It is also apparent that the GSB of the passivated NCs decays with a well-defi ned lifetime, which agrees well with the luminescence lifetime observed in other spectroscopic experiments on PbSe NCs. [93][94][95][96][97] In Figure 3 b, however, the corresponding GSB of the unpassivated NCs has a component that persists for longer than 10 µs. We summarize the kinetics for these bleach signatures in Figure 3 c. To interpret the differences in the TA signals, we consider the origin of the ground state bleach in this sample.…”
Section: Excited State Dynamicsmentioning
confidence: 93%
“…It is also apparent that the GSB of the passivated NCs decays with a well-defi ned lifetime, which agrees well with the luminescence lifetime observed in other spectroscopic experiments on PbSe NCs. [93][94][95][96][97] In Figure 3 b, however, the corresponding GSB of the unpassivated NCs has a component that persists for longer than 10 µs. We summarize the kinetics for these bleach signatures in Figure 3 c. To interpret the differences in the TA signals, we consider the origin of the ground state bleach in this sample.…”
Section: Excited State Dynamicsmentioning
confidence: 93%
“…The semi-classical Marcus model proposed by our group can account for these changes in surface emission. (7,28) We have shown that the energy barrier for charge carriers from the core excitonic state to the emissive surface 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 potential explanation is that the Z-type bond changes the electronic environment of hole traps localized in their vicinity and thus increases the radiative recombination rate by increasing the wavefunction overlap of the localized hole and the core delocalized electron. In addition, it has been shown that the removal of Z-type ligands from surface chalcogenide sites leads to a higher susceptibility for adventitious adsorbates that form non-radiative trap complexes.…”
Section: Toc Graphicsmentioning
confidence: 98%
“…In the temperature range of 75 K through 175 K, within the experimental uncertainty, the PL intensity remains constant. While discussing the influence of surface charge trapping on the PL intensity, similar behavior is reported in case of CdS NCs and is attributed to the balance between charge carriers from the core and surface levels [25]. Comparison of the plot in Fig.…”
Section: (C) Along With the Relative Positions Of Fermi Level In Bulkmentioning
confidence: 64%